The pen and the people English letter writers 1660-1800 - Whyman, Susan E., 1937- (Oxford University Press, 2009)
Capturing actual dialogues of people discussing subjects as diverse as marriage, poverty, poetry, and the emotional lives of servants, 'The Pen and the People' will be enjoyed by everyone interested in history, literature, and the intimate experiences of ordinary people.